1992
DOI: 10.1103/physrevb.45.7772
|View full text |Cite
|
Sign up to set email alerts
|

Neutron-diffraction studies of the nuclear magnetic phase diagram of copper

Abstract: We have studied the spontaneous antiferromagnetic (AF) order in the nuclear spin system of copper by use of neutron-diffraction experiments at nanokelvin temperatures. Copper is an ideal model system as a nearest-neighbor-dominated spin-2 fcc antiferromagnet. The phase diagram has been investigated by measuring the magnetic-field dependence of the (100) reflection, characteristic of a type-I AF structure, and of a Bragg peak at {0 3 3 ). The results suggest the presence of high-field (100) phases at 0. 12 (8 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(39 citation statements)
references
References 34 publications
2
37
0
Order By: Relevance
“…Subsequent susceptibility and neutron-diffraction measurements on a single-crystal specimen have given more insight into the process by which irreversibility occurs. The entropy increase ⌬Sϭ0.12R ln4 was found to occur in a field around 0.1 mT Huiku et al, 1986;Annila et al, 1992), where a phase transition also takes place from the antiferromagnetic phase AF2 to AF1; see the phase diagram of Fig. 1.…”
Section: Metastability and Nonadiabatic Phenomenamentioning
confidence: 94%
See 3 more Smart Citations
“…Subsequent susceptibility and neutron-diffraction measurements on a single-crystal specimen have given more insight into the process by which irreversibility occurs. The entropy increase ⌬Sϭ0.12R ln4 was found to occur in a field around 0.1 mT Huiku et al, 1986;Annila et al, 1992), where a phase transition also takes place from the antiferromagnetic phase AF2 to AF1; see the phase diagram of Fig. 1.…”
Section: Metastability and Nonadiabatic Phenomenamentioning
confidence: 94%
“…This time, however, polarization losses were attributed to the ordering process rather than thermal mixing, and field sweeps between Bϭ1 mT and zero field in the disordered state, at entropies above 0.61R ln4, were found to be adiabatic. Neutrondiffraction experiments (Annila et al, 1992) have clearly shown that, indeed, during the transition from the (1 0 0) phase to the (0 2 3 2 3 ) phase in fields around B ϭ0.11 mT, a large nonadiabaticity occurs. There should, however, be some polarization loss caused by thermal mixing, too, although it may occur in fields above Bϭ1 mT.…”
Section: F Nonadiabaticitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The face centered cubic (fcc) Heisenberg antiferromagnet with short-ranged exchange is a problem which first attracted theoretical attention several decades ago [11], and still continues to be of contemporary interest because the frustration inherent to the fcc lattice leads to a rich variety of magnetic phases [12]. The fabrication by MBE of stuctures containing the zinc-blende phase of MnSe [13] and MnTe [14] provides an opportunity to revisit the problem of the fcc antiferromagnet in the context of symmetry-breaking strain fields and dimensional crossover.…”
Section: Static Spin Organization: Strain-engineered Antiferromagnetismmentioning
confidence: 99%